Comparison Of Intracuff Air Saline 2 Percent Lignocaine Alkalized Lignocaine 2 Percent To Prevent Sore Throat In Patients With General Anaesthesia By Endotracheal Intubation (Indian Journal of Applied-Basic Medical Sciences, 2021)
BACKGROUND: Postoperative Sore throat and cough during emergence are common side  effects of general anaesthesia and its incidence is reported by 30-80% of patients after tracheal  intubation. Also, not to forget the hemodynamic fluctuations associated with it, adds on to the  magnitude of the problem. Thinking of a simple and cost-effective way to tackle this problem,  this study was undertaken to determine the benefits of using intra-cuff lignocaine, alkalized  lignocaine to prevent post intubation sore throat and emergence cough.  AIMS & OBJECTIVE: The objective of this study was to assess the efficacy of intra-cuff 2%  lignocaine solution, intracuffed alkalized lignocaine 2% in reducing emergence cough and  post-operative sore throat after extubation in general surgery patients intubated for 2-4 hours.  METHODS: In a comparative observational study done in tertiary care hospital, where 200  ASA I and II status patients divided into 4groups of 50 each were compared for Sore throat,  throat pain, cough& restlessness. In group A, ETT cuff was filled with air, ingroup B with  Normal saline, in group C 2% plain lignocaine solution, in group D Alkalinised 2% lignocaine  9 cc 2% lignocaine with 1cc sodabicarb 8.5%w/w was used. Side effects like sore throat,  coughing and restlessness were assessed. Chi square and ANOVA test were used to compare  the findings.  RESULTS: Postoperative sore throat (POST), cough, restless ness, throat pain are least with  Alkalized Lignocaine, & then in decreasing order with Lignocaine, saline& air groups. CONCLUSIONS: This study proves that 2% intra-cuff alkalized lignocaine is an effective  method in reducing post-operative sore throat and emergence cough.
Keywords: Intra-cuff air; Intracuff alkalised 2% lignocaine; Lignocaine 2%, saline; POST (Post-Operative Sore Throat)